The Effect of Group Counseling on Reducing Burnout Rates in Disaster Management Officers - Hening Rahmadina; Siti Qodariah; Lilim Halimah (Eduvest - Journal of Universal Studies, 2025)
Burnout is often experienced by individuals who work in the field of humanitarian services and close to the community because work that is oriented towards serving others forms a one-way relationship between the provider and recipient of services. Burnout is characterized by a cold, unpleasant work atmosphere, decreased commitment to the organization, suboptimal work performance and achievements, and often causes officers to distance themselves from their environment. This study aims to identify the effect of group counseling on reducing burnout levels in disaster management officers who are members of the Sukabumi’s Regional BPBD. The burnout theory used in this study is Maslach's theory which consists of three aspects, namely exhaustion, depersonalization, and low of personal achievement. The research method used was Quasi Experiment with one group pretest-posttest research design with a total sample of 6 disaster management officers consisting of 4 women and 2 men who were taken using purposive sampling technique. The measuring instrument used is MBI-HSS which consists of 22 items. The results showed that group counseling influenced on reducing burnout levels by 23.7%. The statistical analysis using the Paired Samples t-Test test shows the p value= 0.0001 and 0.019<0.05 which indicates that group counseling influences on reducing the level of burnout in the exhaustion and depersonalization aspects. Meanwhile, the p-value score=0.830>0.05 indicates that group counseling has no effect on reducing burnout levels in the low of personal achievement aspect.